The Effect of Live Shopping Features on Purchasing Decisions and Perceived Ease of Use in Shoppe and Tokopedia - Frinsis Anastasia Prahita Damayanti; I Made Bayu Dirgantara (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
Technological advancements drive e-commerce innovation, including live shopping features that enhance product evaluation and visualization. This study examines the effect of live shopping features on consumers’ purchasing decisions and perceived ease of use. It also tests whether perceived ease of use mediates the relationship between live shopping features and purchasing decisions, and whether trust moderates the relationship between live shopping features and purchasing decisions. A quantitative design is used based on survey data from users experienced with live shopping features, and the data are analyzed using Structural Equation Modeling (SEM) to test the hypotheses. Based on the results of a study involving 100 respondents who are Shopee and Tokopedia consumers, it can be concluded that live shopping does not directly influence consumers’ purchase decisions on either Shopee or Tokopedia. However, live shopping significantly improves consumers’ perceived ease of use on both platforms. Perceived ease of use significantly mediates the relationship between live shopping and purchase decisions only on Tokopedia, whereas no significant mediating effect is found on Shopee. In addition, trust does not significantly moderate the relationship between live shopping and purchase decisions on either platform. Therefore, Tokopedia should continue enhancing the usability of its live shopping features, while Shopee should consider additional strategies beyond usability improvements to encourage consumers’ purchase decisions.